A Multicomponent Polymer-Metal-Enzyme System as Electrochemical Biosensor for H2O2 Detection - Tong, Pengfei; Asif, Muhammad; Ajmal, Muhammad; Aziz, Ayesha; Sun, Yimin (Frontiers in Chemistry, 2022)
Herein, Au nanoparticles-polydopamine-poly acrylic acid-graphene (Au NPs-PDA-PAA-graphene) multicomponent nanohybrid is fabricated by surface functionalization of graphene alongside extensive in-situ growth of Au nanoparticles. The as-obtained nanocomposite possesses good hydrophilicity, excellent biocompatibility and high biomolecules loading capacity, which acts as an ideal platform for enzyme modification. Considering this fact, Horseradish peroxidase (HRP) is expressively immobilized upon Au NPs-PDA-PAA-graphene surface, in order to lay the foundations of a biosensor that is majorly based on enzymatic activity. The biosensor exhibits higher sensitivity towards the determination of H2O2 with linearity ranging from 0.1 μM upto 20 mM, and the limit of detection going down to 0.02 μM. Encouraged by its acceptable electrocatalytic performance, this multicomponent system can also be easily employed for carrying out the real-time tracking of H2O2 coming out of Macrophage cells. Therefore, this work designs an extraordinarily updated platform for biosensing related applications, also presents a reliable platform for the direct detection of H2O2 in vivo and in vitro, which show great potential in bioelectroanalytical chemistry, cellular biology and pathophysiology.